2019
DOI: 10.24136/eq.2019.032
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between TFP and innovation performance: evidence from EU regions

Abstract: Research background: Total factor productivity (TFP) determines how efficiently and intensely the available inputs are used and combined in production process. Improvement of TFP performance requires identification of its determinants, thus enabling policy actions to focus on them. Since the ability to create and absorb innovation is considered as a crucial factor of economic development, the investigation of the impact of the level of regional innovative performance on TFP distribution across EU regions is an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
1
13
0
2
Order By: Relevance
“…The authors observed that higher innovation intensity is associated with more incredible productivity growth (in both sectors). The positive impact of innovation on productivity, expressed in TFP -Total Factor Productivity, was also observed in the research carried out by Kijek and Matras-Bolibok (2019).…”
Section: Introductionsupporting
confidence: 57%
“…The authors observed that higher innovation intensity is associated with more incredible productivity growth (in both sectors). The positive impact of innovation on productivity, expressed in TFP -Total Factor Productivity, was also observed in the research carried out by Kijek and Matras-Bolibok (2019).…”
Section: Introductionsupporting
confidence: 57%
“…The changes caused by the progressing globalization mainly concern the increase in interdependence between economies, changes in the functioning of selected markets and institutional changes [4][5][6][7][8]. Undoubtedly, the globalization processes have led to systematic socio-economic development in most world economies, combined with a significant increase in the level of innovation, the level of investment outlays and the level of foreign direct investment [9][10][11][12][13][14][15][16]. Globalization processes have also contributed to the emergence of new lifestyles and consumption styles [17][18][19][20], which together with the increase in the wealth of the society and the level of innovation in enterprises contributed to the creation of the renewable energy (RE) sector, which is one of the fastest developing branches of the world economy [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The Regional Innovation Scoreboard (RIS) includes a broad comparative analysis, with regard to the performance of innovation in different regions/countries of the EU, as well as other regions/countries neighboring the EU. Specifically, it shows the impacts on the economy resulting from innovation activities (Kijek and Matras-Bolibok, 2019). RIS classifies countries/regions into four distinctive groups of innovation performance: Leader, Strong, Moderate, Modest (RIS, 2016).…”
Section: Contributions and Practical Implicationsmentioning
confidence: 99%